Abstract

An interferometer comprising three diffraction gratings and an imaging system is used with spatially and spectrally noncoherent light to produce high fidelity low noise recording of phase- and -amplitude objects.

© 1981 Optical Society of America

Full Article  |  PDF Article

References

  • View by:
  • |
  • |
  • |

  1. G. E. Sommargren, B. J. Thompson, Appl. Opt. 12, 2385 (1973).
    [CrossRef]
  2. G. Roblin, M. Sherif, Appl. Opt. 19, 4247 (1980).
    [CrossRef] [PubMed]
  3. O. Bryngdahl, A. Lohmann, J. Opt. Soc. Am. 60, 281 (1970).
    [CrossRef]
  4. E. N. Leith, G. J. Swanson, Appl. Opt, 19, 638 (1980).
    [CrossRef] [PubMed]

1980 (2)

1973 (1)

G. E. Sommargren, B. J. Thompson, Appl. Opt. 12, 2385 (1973).
[CrossRef]

1970 (1)

Bryngdahl, O.

Leith, E. N.

E. N. Leith, G. J. Swanson, Appl. Opt, 19, 638 (1980).
[CrossRef] [PubMed]

Lohmann, A.

Roblin, G.

Sherif, M.

Sommargren, G. E.

G. E. Sommargren, B. J. Thompson, Appl. Opt. 12, 2385 (1973).
[CrossRef]

Swanson, G. J.

E. N. Leith, G. J. Swanson, Appl. Opt, 19, 638 (1980).
[CrossRef] [PubMed]

Thompson, B. J.

G. E. Sommargren, B. J. Thompson, Appl. Opt. 12, 2385 (1973).
[CrossRef]

Appl. Opt (1)

E. N. Leith, G. J. Swanson, Appl. Opt, 19, 638 (1980).
[CrossRef] [PubMed]

Appl. Opt. (2)

G. E. Sommargren, B. J. Thompson, Appl. Opt. 12, 2385 (1973).
[CrossRef]

G. Roblin, M. Sherif, Appl. Opt. 19, 4247 (1980).
[CrossRef] [PubMed]

J. Opt. Soc. Am. (1)

Cited By

OSA participates in CrossRef's Cited-By Linking service. Citing articles from OSA journals and other participating publishers are listed here.

Alert me when this article is cited.


Figures (3)

Fig. 1
Fig. 1

Three-grating interferometer with imaging system.

Fig. 2
Fig. 2

Imaging of noise. G.I. is grating interferometer.

Fig. 3
Fig. 3

Experimental results: (a) incoherent light; (b) coherent light.

Equations (14)

Equations on this page are rendered with MathJax. Learn more.

I = a 0 e ( i 2 π f 0 x ) + a e ( i ϕ ) 2 = a 0 2 + a 2 + 2 a 0 a cos ( 2 π f 0 x - ϕ )
f 1 d 1 + ( f 1 - f 2 ) d 2 + ( f 1 - f 2 - f 3 ) d 3 = 0 ,
d 1 f 1 2 + d 2 ( f 1 - f 2 ) 2 + d 3 ( f 1 - f 2 - f 3 ) ( f 1 - f 2 + f 3 ) = 0
I = u 0 a e ( i ϕ ) + u R a e ( i ϕ ) 2 = a 2 u 0 + u R 2 ,
I = I 0 + I R a 2 + 2 I 0 I R a ( x M , y M ) cos [ 2 π f 1 M x - ϕ ( x M , y M ) ] ,
I = cos 2 π ( f 1 - 2 f 2 ) x - π λ [ d 1 f 1 ( 2 f 0 + f 1 ) + d 2 ( f 1 - f 2 ) × ( 2 f 0 + f 1 - f 2 ) + d 3 ( 2 f 0 + f 1 ) ( f 1 - 2 f 2 ) ] ,
2 π ( f 1 - 2 f 2 ) x - π λ z ( 2 f 0 + f 1 ) ( f 1 - 2 f 2 ) = C ( a constant ) ,
x = λ ( f 0 + ½ f 1 ) z ,
X = ½ λ ( Δ f 0 + f 1 ) z ,
x = ½ λ ( - Δ f 0 + f 1 z ) .
P = 1 / 2 f 2 - f 1 .
Δ z = 1 / ( 2 f 2 - f 1 ) Δ θ 0 .
d x / d z = λ f 1 ( f 1 - f 2 ) / 2 f 1 ,
Δ z = f 1 / ( f 2 - f 1 ) ( 2 f 2 - f 1 ) Δ λ .

Metrics